Expression of the genes encoding hypothalamic feeding-related neuropeptides in the streptozotocin-induced diabetic rats with variable hyperglycemia and hyperphagia. (June 2019) - Sonoda, Satomi; Yoshimura, Mitsuhiro; Ueno, Hiromichi; Nishimura, Haruki; Nishimura, Kazuaki; Tanaka, Kentaro; Motojima, Yasuhito; Saito, Reiko; Maruyama, Takashi; Hashimoto, Hirofumi; Okada, Yosuke; Tanaka, Yoshiya; et al.
Highlights: We examined the hypothalamic feeding-related neuropeptides in diabetic rats. STZ-induced diabetic rats exhibit hyperphagia in a blood glucose dependent manner. Dynamic regulation of these genes was associated with plasma glucose/insulin. These genes were differentially expressed depending on the glucose/insulin.